Psychological Impact on Health Officer Providing Treatment of COVID-19 - Fitriya Fajar Wati; Rahmania Ambarika (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
During the first week of March, the spike in 2019 coronavirus disease (COVID-19) cases reached more than 100 countries with more than 100,000 cases. Authorized health workers have initiated awareness and preparedness activities out of bounds. Recently, the Covid-19 pandemic has resulted in a decline in mental health for every person or group of people, even the wider community, including medical personnel. the purpose of this study is to determine the Psychological impact of Health Workers during the COVID-19 pandemic. This study is a literature review by comparing articles, journals or secondary data from previously published literature contained in the medical journal database Science Direct, PubMed and ClinicalKey. In conclusion, it found the prevalence of psychological impacts such as stress, anxiety and depression from mild to severe among health workers during the COVID-19 pandemic. These findings will help improve our understanding of the impact or impact of the COVID-19 pandemic on the Psychology of Health Worker.